Chronic Mild Stress: um estudo sobre a interação entre submissão ao protocolo de estressores, comportamento operante e privação - Pereira, Clarissa Moreira (2009)
Chronic Mild Stress (CMS) is an experimental model that attempts to reproduce, in laboratory, real life stressing conditions in rats, by using a stress protocol to study the effects of the exposition to these stressors in the subjects behavior. In the present experiment, the purpose was to identify if whole protocol, and not some of the stressor stimuli specifically (water and food deprivation) are responsible for producing the effects frequently described in literature (decreased sweet substance ingestion and preference and body weight when submitted to the protocol). It was also verified the influence of operant concurrent schedule sessions (water-sucrose) in all the effects considered. The results were described on (a) body weight, (b) food and water consumption, (c) sucrose ingestion and preference, and (d) concurrent schedule performance. Deprivation itself and incomplete protocol (with no deprivation conditions) produced effects on body weight, food and water consumption, and sucrose preference and ingestion. However, the two together complete protocol showed itself to be critical to produce these results. Some operant behavior features differ depending on whether the subjects are deprived or not before the session, but they don t among subjects that are submitted to the other stressors (other than deprivation). According to these results, there are two possible suggestions: (a) neonatal handling can be responsible for the inexistency of the common effects of the protocol in the subjects behavior; and (b) the continuous exposure to sucrose can have similar effects to analgesia, making it possible that effects of the protocol are not produced. One issue is considered important, considering these results: measures, other than just sucrose ingestion and preference, must be taken into account in CMS studies